Biomarker δ13C values record consistent savanna vegetation and variable alkalinity of Lake Olduvai during Pleistocene wet/dry cycles - Doiron, Kelsey E.; Colcord, Devon E.; Shilling, Andrea M.; Njau, Jackson K.; Stanistreet, Ian G.; Stollhofen, Harald; Schick, Kathy D.; Toth, Nicholas P.; Brassell, Simon C. (Proceedings of the National Academy of Sciences of the United States of America, 2026)
Climate records for the early Pleistocene in eastern Africa aid reconstruction of the ecology and landscapes occupied by hominins. Environmental changes associated with alternating wet/dry cycles during this critical interval in hominin evolution are recorded in isotopic profiles from lake sediments from Olduvai Gorge. The Olduvai Gorge Coring Project targeted the depocenter of Paleolake Olduvai, recovering a stratigraphic succession between the Bed I Basalt ( 1.90 Ma) and Tuff IF ( 1.80 Ma) datums that span hominin fossil horizons in nearby outcrops. Lacustrine claystones from the lower part of this interval are characterized by high Corg (avg. 2.5 %). They display variations in δ13Corg reflecting temporal changes in organic matter (OM) sources. Stratigraphic profiles for n-alkane δ13C values derived from plant waxes are consistent throughout wet/dry cycles indicating stability in savanna vegetation, refuting evidence for increased C4 grasses during drier intervals. δ13C values for n-alkanes derived from aquatic macrophytes and for algal biomarkers increase during drier episodes, reflecting use of bicarbonate as a carbon source triggered by enhanced lake alkalinity. δ13Corg profiles reflect variations in inputs of terrestrial vs. aquatic OM during wet/dry cycles, which are mirrored by δ13C values for hop-17(21)-ene derived from heterotrophic bacteria utilizing sedimentary OM. The δ13C records from Paleolake Olduvai sediments show temporal changes in OM sources rather than shifts in the proportion of C3 and C4 vegetation, indicating that precession-driven climate cycles primarily affected lake environments and associated aquatic resources. Thus, intervals of high climate variability did not necessarily cause changes in savanna vegetation affecting hominin habitats.
CRIS-Team Scopus Importer:2026-01-09
Keywords: alkenones; carbon isotopes; hopanoids; plant wax; steroids